2019
DOI: 10.1111/aos.14310
|View full text |Cite
|
Sign up to set email alerts
|

The tolerance of anisometropia

Abstract: Purpose: This study examines aniseikonia, Aniseikonia tolerance range (ATR), anisometropia and patient-reported outcomes (PRO) in an anisometropic population compared with a non-anisometropic population. The relationship between anisometropia and aniseikonia is determined, and the correlations between aniseikonia, anisometropia and ATR versus PRO are described. Methods: One hundred and twenty-three patients with IOL-induced anisometropia ≥1 dioptre (D) (the anisometropic group) and 17 patients who had IOL-indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
2
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 33 publications
1
18
2
4
Order By: Relevance
“…In this study, we found a high percentage of patients with poor stereoacuity and thus unmeasurable ATR (31% TNO and 47% RAN-DOT). Among the patients with measurable ATR, we found that the proportion of low ATR was significantly higher than that reported in earlier studies examining IOL-induced anisometropic patients (Krarup et al in review;Krarup et al, 2019). Contrary to our expectations, ATR was not correlated with PROs.…”
Section: Discussioncontrasting
confidence: 99%
“…In this study, we found a high percentage of patients with poor stereoacuity and thus unmeasurable ATR (31% TNO and 47% RAN-DOT). Among the patients with measurable ATR, we found that the proportion of low ATR was significantly higher than that reported in earlier studies examining IOL-induced anisometropic patients (Krarup et al in review;Krarup et al, 2019). Contrary to our expectations, ATR was not correlated with PROs.…”
Section: Discussioncontrasting
confidence: 99%
“…Although a cross-cultural adaptation for the Spanish language has been made using the Rasch method, 52 the original questionnaire 9 was not validated using this method. Several authors have used the CISS for other visual dysfunctions, 53 56 but this is not an appropriate approach because a questionnaire should only be used for the specific condition for which it was developed and validated. 57 , 58 In fact, other studies in the literature have reported difficulties when applying the CISS to other visual conditions, different from convergence insufficiency.…”
Section: Discussionmentioning
confidence: 99%
“…The CISS is valid tool which is used to discriminate between convergence insufficiency and normal binocular vision in patient-reported outcomes [ 12 ]. It was used with patients with anisometropia or aniseikonia too [ 13 ].…”
Section: Introductionmentioning
confidence: 99%